Pemberian Hak Hadanah Kepada Ibu Tiri dalam Putusan Pengadilan Agama Sidoarjo Nomor: 0763/Pdt.G/2018/Pa.Sda Perspektif Maslahah Mursalah - Firyal, Wafda (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2019)
This article is a library research on the granting of rights to stepmothers in the decision of the Sidoarjo Religious Court Number: 0763/Pdt.G/2018/PA.Sda. The research data are collected using documentation techniques and are analysed using descriptive analysis techniques and using a deductive mindset that is by outlining the decision of the Sidoarjo Religious Court which is then reviewed from the perspective of maslahah mursalah. The panel of judges in determining the right of gift to stepmothers in the Sidoarjo Religious Court's decision, based on article 41 letter (a) of Law Number 1 of 1974 jo. article 105 and article 156 letter (a) Compilation of Islamic Law and the proposition in the book Bajuri juz II. In addition, a willingness from the Defendant who is the biological father of the child to give the right of gift to the Plaintiff's Reconstruction is a point that is included as consideration by the panel of judges. In Islamic law which is examined from the theory of maslahah mursalah, the judge's consideration to establish the right of hadanah to the stepmother in the Sidoarjo Religious Court's ruling is in accordance with the purpose of the hadanah namely to prioritize the interests and benefit of the child so that later he or she can grow into a good person under the care of an appropriate person, even though the child is not a biological child of the Reconvention Plaintiff, the Reconvention Plaintiff is in fact more feasible and competent to have the right of hadanah. [Artikel ini merupakan hasil penelitian pustaka (library research) tentang pemberian hak hadanah kepada ibu tiri dalam putusan Pengadilan Agama SidoarjoNomor: 0763/Pdt.G/2018/PA.Sda”. Data penelitian dihimpun dengan menggunakan teknik dokumentasi dan dianalisis dengan menggunakan teknik deskriptif analisis yang menggunakan pola pikir deduktif yaitu dengan cara menguraikan putusan Pengadilan Agama Sidoarjo yang kemudian dikaji dari perspektif maslahah mursalah. Majelis hakim dalam menetapkan hak hadanah kepada ibu tiri pada putusan Pengadilan Agama Sidoarjo, didasarkan pada pasal 41 huruf (a) UndangUndang Nomor 1 Tahun 1974 jo. pasal 105 dan pasal 156 huruf (a) Kompilasi Hukum Islam serta dalil dalam kitab Bajuri juz II. Selain itu, adanya kerelaan dari Tergugat Rekonvensi yang merupakan ayah kandung dari anak tersebut untuk memberikan hak hadanah kepada Penggugat Rekonvensi merupakan point yang dimasukkan sebagai pertimbangan oleh majelis hakim. Dalam hukum Islam yang dikaji dari teori maslahah mursalah, pertimbangan hakim untuk menetapkan hak hadanah kepada ibu tiri pada putusan pengadilan Agama Sidoarjo, telah sesuai dengan tujuan dari hadanah yaitu mengutamakan kepentingan dan kemaslahatan anak agar nantinya dapat tumbuh berkembang menjadi pribadi yang baik dibawah pengasuhan orang yang tepat, walaupun anak tersebut bukan merupakan anak kandung dari Penggugat Rekonvensi namun Penggugat Rekonvensi nyatanya lebih layak dan berkompeten untuk memiliki hak hadanah.]